2023
DOI: 10.3390/foods12030473
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Recent Application of Chemometrics in Quality Analysis and Characterization of Bee Honey during Processing and Storage

Abstract: The application of chemometrics, a widely used science in food studies (and not only food studies) has begun to increase in importance with chemometrics being a very powerful tool in analyzing large numbers of results. In the case of honey, chemometrics is usually used for assessing honey authenticity and quality control, combined with well-established analytical methods. Research related to investigation of the quality changes in honey due to modifications after processing and storage is rare, with a visibly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 256 publications
0
15
0
Order By: Relevance
“…The obtained results of physicochemical parameters of 609 honey samples were presented by descriptive analysis of the results obtained for different botanical origins of honey samples (Table 1), different years of harvest (Table 2), and different regions of the harvested samples (Table 3). Based on Table 1, there were six types of honey identified: acacia (213 samples), honeydew (29), linden (34), monofloral (8), polyfloral (302), and sunflower honey (23). In Table 2, the data show that 209 samples were collected in 2018, followed by 80 samples in 2019, 78 samples in 2020, 108 samples in 2021, and 113 samples in 2022, with an additional 21 collected in 2023.…”
Section: Physicochemical Characterizationmentioning
confidence: 99%
See 3 more Smart Citations
“…The obtained results of physicochemical parameters of 609 honey samples were presented by descriptive analysis of the results obtained for different botanical origins of honey samples (Table 1), different years of harvest (Table 2), and different regions of the harvested samples (Table 3). Based on Table 1, there were six types of honey identified: acacia (213 samples), honeydew (29), linden (34), monofloral (8), polyfloral (302), and sunflower honey (23). In Table 2, the data show that 209 samples were collected in 2018, followed by 80 samples in 2019, 78 samples in 2020, 108 samples in 2021, and 113 samples in 2022, with an additional 21 collected in 2023.…”
Section: Physicochemical Characterizationmentioning
confidence: 99%
“…In honey samples, the ratio of glucose and fructose within the total content of monosaccharides should be approximate, with a higher fructose proportion [34,35]. Additionally, fructose and glucose ratios could be used to differentiate monofloral types of honey [9].…”
Section: Glucose Fructose and Sucrose Contentmentioning
confidence: 99%
See 2 more Smart Citations
“…Conventionally, raw honey is processed at temperature of 45–80 °C for 1–45 min (Subramanian et al ., 2007) to delay crystallisation, to reduce viscosity, to remove contaminating microbes and to prevent fermentation (Subramanian et al ., 2007; Scepankova et al ., 2021). However, heat treatment is a processing method that is often accompanied with significant degradation of food quality, particularly raw honey (Wang et al ., 2004; Soni et al ., 2016; Tarapoulouzi et al ., 2023). Samborska & Czelejewska (2014) reported that multifloral honey processed at 90 °C for 30 min contained a high hydroxymethylfurfural (HMF) concentration of 67.8 mg/kg.…”
Section: Introductionmentioning
confidence: 99%